The Strategies of Cultivating Mathematical Thinking Ability in Primary School Mathematics Teaching - Zhang, Haizhen (Journal of Education and Educational Technologies, 2023)
The ability of mathematical thinking refers to that students use their own mathematical thinking and logical ability to solve mathematical problems, fully develop reasonable imagination, and then summarize and summarize the methods to solve specific mathematical problems based on their own mathematical knowledge. Therefore, it is necessary to strengthen the cultivation of primary school students' mathematical thinking ability. And mathematics is a subject with strong logic thinking. However, due to the young age of primary school students, their thinking ability is limited, their life experience and experience are insufficient, and their knowledge reserve is relatively weak, which makes the primary school students' mathematical thinking ability still has a large room for improvement. Therefore, cultivating students' mathematical thinking ability in primary school mathematics teaching can not only improve learning efficiency, enable students to fully understand and firmly grasp the mathematical knowledge they have learned, and apply mathematical knowledge to solving practical mathematical problems, but also promote teachers to effectively promote and implement teaching programs. Based on this, this paper expounds the important influence of the cultivation of mathematical thinking ability on primary school mathematics teaching and the basic requirements for the cultivation of mathematical thinking ability in primary school mathematics teaching, and discusses and analyzes the strategies for the cultivation of mathematical thinking ability in primary school mathematics teaching.